Strategi Telemarketing yang Efektif: Analisis Pengaruhnya terhadap Minat Beli Mobil Hino di PT Indo Mobil Prima Niaga - Yusditara, Wisnu; Nurdelila; harahap, Nirmala Haty (Jurnal KAFEBIS, 2025)
Telemarketing, as one of the marketing communication methods, plays a crucial role in product introduction and fostering customer relationships in the era of advancing communication technology. This study aims to analyze the effectiveness of telemarketing as a marketing strategy at PT Indo Mobil Prima Niaga and the role of telemarketing in supporting after-sales services at PT Hino Motors Sales Indonesia. The research employs a descriptive qualitative approach, collecting data through interviews and observations. The findings reveal that telemarketing functions not only as a tool for sales promotion but also as an interactive communication medium that enhances customer satisfaction and loyalty. This research contributes to a better understanding of the importance of telemarketing in developing effective and sustainable marketing strategies in the automotive sector.